A Cornucopia of Iridium Nitrogen Compounds Produced from Laser‐Ablated Iridium Atoms and Dinitrogen. Issue 33 (26th May 2020) - Stüker, Tony; Beckers, Helmut; Riedel, Sebastian
Abstract: Invited for the cover of this issue is the group of Sebastian Riedel at Freie Universität Berlin. The image depicts an iridium rainbow reacting with dinitrogen to form iridium–nitrogen compounds. Read the full text of the article at 10.1002/chem.201905514 . Abstract : " The idea was to produce a neutral compound containing iridium in oxidation state +IX by using three terminal nitrido ligands, each of which potentially raise the oxidation state of the metal center by three ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 7384 ff. (DOI: 10.1002/chem.201905514 ).